PENGARUH SENAM BEBEK BERENANG TERHADAP MOTORIK KASAR ANAK DI TK NEGERI PEMBINA KOTO BARU KEC. KOTO BARU KAB. DHARMASRAYA - Enawati Enawati; Fitria Sari; Ayu Mustika Sari (Dharmas Journal of Sport, 2021)
This study aims to see the effect of duck swimming gymnastics activities on children's gross motor skills at Pembina State Kindergarten, Koto Baru, Kec. New Koto Kab. Dharmasraya, using a quasi-experimental design with a non-equivalent control group design. The population of all TK Negeri Pembina Koto Baru Kec. New Koto Kab. Dharmasraya as many as 31 children. The selected sample is 15 children, using Saturated Sampling. This data collection uses the observation method which is carried out in the second semester of the 2020/2021 academic year in 4 days. The results showed that through learning before the implementation of duck swimming gymnastics obtained an initial assessment with an average of 61.72. The results of the final assessment after being given treatment, namely through duck swimming, the average value was 74.22. So it can be concluded that duck swimming has a significant effect. So that the results of the calculation of sig < or 0.003 < 0.05 for the gross motor skills of children at the Pembina Koto Baru State Kindergarten, which means that the t test is not accepted or Ho is rejected and Hα is accepted.